For a New and Bright Future: Propaganda in Hungarian Newsreels Between 1945 and 1954 - Somogyvári, Lajos (Historia y Memoria de la Educación, 2022)
This study firstly emphasize the importance and relevance of analysing newsreels from a history of education aspect, which is a blind spot in the Hungarian research. The official Leninist ideology deeply influenced the genre, used as a channel of overall propaganda, during and after the communist takeover, between 1945 and 1954. Production and broadcasting depended on the political goals and turns of the Communist Party, combined simple messages with easily understandable narrative forms, to support campaigns, spread intended knowledge and so on. The footages has now digitized and open to access for everyone (https://filmhiradokonline.hu/): using the webpage, through a three-step data collecting and selection process, a database made, with 205 items to analyse. Three archetypes, basic storytelling forms are detected, I called them metaphorically One from the many, Occupying space and Learning society. The development and progression of the country after WW2 always represented in individual life-stories and personal backgrounds to get close these stories to the audience, trying to make Soviets and communists more popular. At the same time, more and more spaces are occupied by the new power, both physically and symbolically, for example the former castles became schools, training sites, etc., which signed the expropriation the past, too. Definition and scope of education extended in the discourses, because every member of the society would learn repeatedly the language of the new establishment. Propaganda and persuasion was overall in this process, one could not avoid interacting and reflecting somehow to this.